The Effectiveness of Guided Inquiry Model and Problem Based Learning(PBL) in Learning to Write Narrative Text in terms of Cognitive Learning Outcomes of Class V Elementary School Students. - Dwi Kurniati Widiastuti; Murtono Murtono; Mohammad Kanzunnudin (Universitas Muria Kudus, 2021)
The objectives of this research are (1) testing the effectiveness of using guided inquiry models in learning to write narrative text for fifth grade school students on cognitive learning outcomes; (2) testing the effectiveness of using the PBL model in learning to write narrative text for fifth grade elementary school students on cognitive learning outcomes; This type of research design is a Quasi Experiment Design. he results showed a significance value (2-tailed) of 0.003 <0.005. This means that there are differences in the effectiveness of cognitive learning outcomes between the experimental class treated with the Guided Inquiry learning model, and the control class treated with the Problem Based Learning learning model. The posttest average score of the Guided Inquiry learning model is 83.75, while the average value of the Problem Based Learning learning model is 80.31.